Proceedings from the SAE Highway Tire Noise Symposium, November 10-12, 1976, San Francisco. (Society of Automotive Engineers, 1977)
1- Heavy truck tire selection and use. 2- Functional requirementes for light vehicle tires.3- Tire sound measurement.